Urgensi Perencanaan Pendidikan Islam Pasca Pandemi Covid-19 - Akhmad Akhmad (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
Planning will be considered mature and good, if it meets the requirements and elements in the planning itself. Planning has an important position in an organization. Without planning, the course of the organization will not have a clear direction and purpose. Education planning must be done when COVID-19 occurs in Indonesia. In the field of education, the impact of COVID-19 has not been spared, so the Minister of Education and Culture of the Republic of Indonesia Nadiem Anwar Makarim issued Circular No. 4 dated March 19, 2020 regarding the implementation of education in the emergency period of the spread of COVID-19. The purpose of this study is to explain the urgency of planning Islamic education after COVID-19. The method in this study uses a qualitative method with the type of descriptive analytic research. The results in this study are that Islamic education planning in Distance Learning Learning from Home Online (PJJ BDR Daring) due to COVID-19, begins with student readiness, prepares an Online Learning Implementation Plan (RPPD), uses strategies in learning, uses learning media, learning methods, learning resources and teaching materials, time allocation, and assessment of formative learning outcomes.